(untitled) (Clío & Asociados. La historia enseñada. ISSN: 2362-3063, 2018)
In this work we present a teaching-learning experience that we developed as initial formation teachers with young students that are doing the second year of the Geography professorship course of studies in the ISFD (Superior Institute of Teachers Formation) N° 96 of La Plata, in 2016. From the subject Pedagogic Didactic Perspective II, we deal with the urban space as an object of study through two analytic categories: territorial marks and memorials; and then we transform it in an object of teaching from the contribution of the Specific Didactics in Social Sciences and Geography. We selected and analyzed a work made by students about Parque Castelli and its surroundings, places in which there are different territorial marks, such as a monument and murals that inform on the flood occurred in the city on the 2nd April 2013 and they commemorate its victims. The experience let us reflect on the teaching of the city from the topics and points of view proposed, question spatial conceptions and geographic imaginaries constructed and acknowledge ourselves as citizens that produce spaces with rights to inhabit the city.